An Analysis of Business Model Innovation Through the Digital Transformation of Household Appliance Manufacturing Companies in Shandong, China - Yan, Songsong; Ani, Teodorica (International Journal of Global Economics and Management, 2024)
This study intends to analyze the influence of digital transformation on Shandong home appliance manufacturing companies’ business model innovation. Specifically, the study presented the profile of the household appliance manufacturing companies, the extent of business model innovation, and level of digital transformation adoption. The study intends to analyze the effect of digital transformation to business model innovation. Also, this aims to know which among the factors significantly effect on business model innovation. The study determines the significant differences in the assessments of respondents when grouped according to profile. The study intends to propose a business innovation program for household appliance manufacturing companies. The study utilized descriptive research method. A total of 81 companies were the target respondents out of 101 total number of companies. The impact of product supply, customers, resources, capabilities, and strategies on business model innovation were deeply analyzed, including value proposition, operational value, human capital, and financial value. The data results met the reliability and validity requirements. This study used frequency, percentage, mean and regression analysis. The study revealed that most of the household appliance manufacturing companies have more than 50 employees and 4-5 years in business operation. There is very great extent of business model innovation in operational value, human capital, and financial value while great extent in value proposition. There is very high digital transformation with regards to product offering, customers, resources, capabilities, and strategy. Digital transformation has significant effect to business model innovation. The strategy significantly affects the business model innovation the most. There is no significant difference on the assessment of the respondents when grouped according to profile. The study proposed a Business Innovation Program for the household manufacturing companies in Shandong, China.